Bunuel wrote:
mmrigank wrote:
I understand the solution,, but what is wrong with this understanding
(x+7)(x−2)/2 => x+7 = odd+odd = even
x-2 => odd -even = odd
(x+7)(x−2) => even*odd = even
even/2 (even) => even
what is wrong with above ?
even/2 is not always even. For example, 2/2 = 1 = odd.Bunuel,
Not matter what is the value of highlighted part, since x+7 is even , then solution will always be even.
Also, what odd value of x will give (x-2) as 2 . It is given that x is odd integer.
Please explain?